On the L/σ Range of the TVFM - P.J.M. Carrott; I.P.P. Cansado; M.M.L. Ribeiro Carrott (Adsorption Science & Technology)
Adsorption isotherms of nitrogen, carbon dioxide, methanol, dichloromethane, benzene and neopentane were determined on a range of molecular sieve and super-activated carbons with the objective of establishing the range of validity of the Theory of Volume Filling of Micropores (TVFM) in terms of the ratio of pore width to molecular diameter, L o /σ. It is shown that, in the absence of molecular-sieving effects, both the characteristic curve concept and the DR equation are valid over the whole of the micropore range, corresponding to values of L o /σ less than or equal to 5 and to at least a slight enhancement in the characteristic energy, E 0 , of the adsorbent when compared with the corresponding value obtained with non-porous carbon blacks. On the other hand, estimation of the mean micropore width was only possible for values of L o /σ up to ca. 2.3, corresponding to at least a two-fold enhancement in E 0 . Results obtained using N 2 at 77 K showed some significant differences to those obtained with organic adsorptives at higher temperature.